The impact of land use in the catchment of Batang Ai and reservoir fisheries on Batang Ai hydro-electric power (HEP) lake - Mancha, anak Bagat (Universiti Malaysia Sarawak (UNIMAS), 2005)
The lack of farm land at Batang Ai Resettlement Scheme had lead to an increased in the number of resettled communities to come back to utilize their former NCR lands which were not submerged by the construction of the hydro-electric power dam. Increased in population of the area resulted in the increased for land use and water resources utilization. Therefore the objectives of this study were to: (i) record the water quality of the lake in accordance to the INWQS, (ii) examine the existing agriculture and reservoir fishery practices at the lake, and (iii) evaluate changes in fish species at the lake and its tributaries. The water quality of the lake, Batang Engkari, and Batang Ai all falls under Class II of DOE WQI which was categorized as good. Under INWQS classification, it falls into Class I to Class III of INWQS which is good to moderate. The result shows that the water of Batang Ai HEP Lake, Batang Engkari and Batang Ai is still viable to support economic activities at that area. The lake has been utilized to cater for the large scale cage culture activities managed by the some community groups, individuals, and government agencies. This study also found that there were changes in the population of fish species of Batang Ai before and after the construction of the dam. A number of fish species of the former river had disappeared and were being replaced by the introduced species in the lake.